Snapping Pes Syndrome Caused by the Gracilis Tendon: Successful Selective Surgery with Specific Diagnosis by Ultrasonography - Manabu Akagawa; Yoshiaki Kimura; Hidetomo Saito; Hiroaki Kijima; Kimio Saito; Toyohito Segawa; Ikuko Wakabayashi; Takeshi Kashiwagura; Naohisa Miyakoshi; Yoichi Shimada (Case Reports in Orthopedics)
We report the case of painful snapping pes syndrome caused by the gracilis tendon. A 26-year-old man presented with acute right knee pain and restricted extension. Although snapping could not be reproduced due to severe pain, the snapping of the gracilis tendon could be specifically diagnosed using ultrasonography and lidocaine injection. Because of the failure of conservative treatment, surgery was performed. The distal attachment of the gracilis tendon was released, and the symptom disappeared quickly. There was no recurrence at the 10-month follow-up.